Effect of plantar cutaneous inputs on center of pressure during quiet stance in older adults - Yun Wang; Kazuhiko Watanabe; Liang Chen (Elsevier, 2016)
Background/Objective: We investigated the effect of plantar cutaneous inputs on the postural sway during quiet standing in older adults. Methods: Eight healthy elderly individuals (age 72.3 ± 4.4 years) stood on a force platform for 30 seconds without and with mechanical facilitation of sensation from the forefoot (a small coin-shaped object under the sole), and their eyes closed. Ellipse area and mean velocity of center of pressure, rambling and trembling trajectories in the anterior-posterior (AP) and medial-lateral directions were analyzed. Results: The ellipse area in the stimulation condition was significantly reduced as compared to the control condition. Significant decreases were also observed in the stimulation condition for the velocity of the center of pressure in both AP and medial-lateral directions and for velocity of the trembling trajectory in the AP direction. Conclusion: The findings indicate that mechanical facilitation of sensation on the plantar soles enhanced postural stability in older adults. The results show that plantar cutaneous inputs provide information that leads to reduced postural sway in healthy older adults. This could have implications in clinical and rehabilitative areas.